2020
DOI: 10.1152/ajpregu.00023.2020
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulator of thirst behavior: phoenixin

Abstract: There are examples of physiological conditions under which thirst is inappropriately exaggerated, and the mechanisms for these paradoxical ingestive behaviors remain unknown. We are interested in thirst mechanisms across the female life cycle and have identified a novel mechanism through which ingestive behavior may be activated. We discovered a previously unrecognized endogenous hypothalamic peptide, phoenixin (PNX), identified physiologically relevant actions of the peptide in brain and pituitary gland to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…PNX also influences the excitability of solitary nucleus neurons, and its action depends on environmental stress factors and glucocorticoids [ 17 ]. PNX stimulates the secretion of vasopressin and is an element of neuronal loops that regulate the endocrine and behavioral mechanisms of electrolyte homeostasis in the body [ 18 ]. Recently, studies have also suggested a neuroprotective effect of PNX-20 dependent on SIRT1 and the participation of this neuropeptide in the modulation of inflammatory reactions in the CNS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…PNX also influences the excitability of solitary nucleus neurons, and its action depends on environmental stress factors and glucocorticoids [ 17 ]. PNX stimulates the secretion of vasopressin and is an element of neuronal loops that regulate the endocrine and behavioral mechanisms of electrolyte homeostasis in the body [ 18 ]. Recently, studies have also suggested a neuroprotective effect of PNX-20 dependent on SIRT1 and the participation of this neuropeptide in the modulation of inflammatory reactions in the CNS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, our group demonstrated upregulation of GPR173 during late post-puberty in the PVN, and importantly, upregulation during the last third of pregnancy in the hypothalamus. Moreover, it was observed an increase in the hypothalamic levels of PNX and AVP across pregnancy compared with levels present during diestrus with a positive correlation between both peptides [84]. Thus, these results suggest an important role of PNX on AVP release during late pregnancy, which can help to provide potential pharmacological targets for preventing the development of cardiovascular diseases across pregnancy.…”
Section: Interaction Between Ovarian Hormones Phoenixin and Avp Releasementioning
confidence: 57%
“…Despite there are no differences between males and females on PNX-induced AVP release, a potential estrogen response element (ERE) upstream of PNX was identified, suggesting that ovarian hormones, especially E2, can modulate PNX [80,83]. Consistent with this idea, ovarian failure induced by OVX induces downregulation of PNX compared with intact females in the hypothalamus [84].…”
Section: Interaction Between Ovarian Hormones Phoenixin and Avp Releasementioning
confidence: 87%
“…Recently, neuropeptidomic searches in arthropod transcriptomes revealed phoenixin precursors with conserved cleavage sites to produce the mature PNX peptide PNX14 and PNX-20 (Nguyen et al 2018). PNX is involved in many different physiological functions in mammals, such as cardio-modulation, memory, anxiety, food intake and reproduction (Clarke and Dhillo 2019;Schalla and Stengel 2019;Billert et al 2020;Haddock et al 2020;Ma et al 2020;Schalla et al 2020;Friedrich and Stengel 2021;Yao et al 2021). The mechanism of signalling of PNX, an orphan ligand, remains unclear.…”
Section: Introductionmentioning
confidence: 99%